2009
DOI: 10.1108/17473610910940783
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing advergames: active diversions or actually deception. An exploratory study of online advergames content

Abstract: PurposeThe purpose of this paper is to review the nature of advergames and the rhetoric versus reality of their claimed effects and effectiveness, focusing specifically on their use by children.Design/methodology/approachA content analysis of major web sites that are likely to have particular appeal to children and an evaluation in order to determine whether the material contained in these sites would be permitted if similar codes of practice, as for other media, would be applied to internet sites.FindingsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
0
40
0
2
Order By: Relevance
“…Así, podemos encontrar una gran diversidad de formatos como mensajes de texto (SMS); mensajes multimedia (MMS) (HSU y HSU, 2007); cupones electrónicos, de igual función que los impresos pero con la personalización y entrega directa que permite el móvil (SCHARL et al, 2005); banners y enlaces en los sitios de Internet móvil; oferta de descargas y aplicaciones gratuitas a cambio de la aceptación de publicidad (VENTURA, 2010); publicidad bluetooth, es decir, mensajes multimedia enviados, no a través de la red móvil, sino a través de bluetooth; y advergames, videojuegos con la marca o producto promocionado como protagonista, con el que se crea un vínculo emocional mediante el entretenimiento (DAHL et al, 2009). Todos estos formatos ofrecen múltiples posibilidades a la creatividad publicitaria, pero también abren nuevas líneas de investigación de cara a estudiar la eficacia de todos ellos para determinar los más idóneos según los objetivos de la campaña.…”
Section: Marketing Y Publicidad Móvilunclassified
“…Así, podemos encontrar una gran diversidad de formatos como mensajes de texto (SMS); mensajes multimedia (MMS) (HSU y HSU, 2007); cupones electrónicos, de igual función que los impresos pero con la personalización y entrega directa que permite el móvil (SCHARL et al, 2005); banners y enlaces en los sitios de Internet móvil; oferta de descargas y aplicaciones gratuitas a cambio de la aceptación de publicidad (VENTURA, 2010); publicidad bluetooth, es decir, mensajes multimedia enviados, no a través de la red móvil, sino a través de bluetooth; y advergames, videojuegos con la marca o producto promocionado como protagonista, con el que se crea un vínculo emocional mediante el entretenimiento (DAHL et al, 2009). Todos estos formatos ofrecen múltiples posibilidades a la creatividad publicitaria, pero también abren nuevas líneas de investigación de cara a estudiar la eficacia de todos ellos para determinar los más idóneos según los objetivos de la campaña.…”
Section: Marketing Y Publicidad Móvilunclassified
“…At about the same time, advergames also appeared [19] representing a more dynamic marketing approach, eventually blurring the lines between entertainment and persuasion [3]. Up to now, advergame research has mainly focused on online / web-based games, primarily targeting children and young(er) adults [3; 25].…”
Section: Background and Related Workmentioning
confidence: 99%
“…On the first day of the exhibition the game was presented on MEGA (TV) Channel, on the morning show with the highest ratings in Greek television 3 . This day, more than 85% of the people visiting the booth mentioned viewing the game on TV.…”
Section: What Went Rightmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent content analysis of child-targeted web sites found that the majority of sites contained material which does not comply with the existing broadcasting codes of practice for mainstream advertising (Dahl et al, 2009). This suggests that interaction with online advertising exposes children to commercial messages which would not be permitted in more familiar (and more thoroughly researched and regulated) media, such as print and television.…”
Section: Advertising In Online Environmentsmentioning
confidence: 99%